The Effect Of Work Motivation And Discipline On Employee Performance At Pt Panca Kharisma Utama - Al Kessa, Muhammad Stefani; Husainah, Nazifah (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the influence of motivation and work discipline on employee performance at PT. Panca Kharisma Utama. As a key factor in achieving organizational goals, effective human resource management is important to improve performance. Motivation and work discipline are two elements that can play a major role in influencing employee performance. This study uses a quantitative method with a descriptive, comparative, and associative approach. Data were obtained through questionnaires distributed to 50 employees, and analyzed using multiple linear regression to determine the effect of each variable on employee performance. The results showed that motivation (X1) and work discipline (X2) significantly influenced employee performance (Y) at PT. Panca Kharisma Utama. The coefficient of determination (R²) of 0.556 indicates that 55.6% of the variation in employee performance can be explained by motivation and work discipline. The partial t-test shows that both variables have a significant positive effect on performance, while the simultaneous F-test indicates that both variables together have a significant effect on employee performance. This study provides recommendations to companies to improve motivation and work discipline in order to achieve more optimal performance.